RESULTS OF SSR ANALYSIS, PROPERTIES OF PLANT MORPHOLOGY AND BIOCHEMICAL COMPOSITION OF CHINESE BROCCOLI – A NEW VEGETABLE CROP FOR RUSSIA - Y. V. Fotev; A. M. Artemyeva; D. A. Fateev; N. B. Naumova; G. A. Bugrovskaya; V. P. Belousova; T. A. Kukushkina (Овощи России)
The results of estimation of growth and development parameters, SSR analysis, electron microscopic examination of the surface of pollen and seeds, biochemical composition (ascorbic acid, carotenoids, carotenes, macro- and microelements content in the stem part of plant) of 8 Chinese broccoli, Brassica oleracea var. alboglabra samples grown in the unheated greenhouse of the Central Siberian Botanical Garden SB RAS, Novosibirsk (54°49′33″ N, 83°06′34″ E) and phy- totron of N. I. Vavilov Institute of Plant Genetic Resources (VIR) have been presented. Through the study, the large surface cellularity of B.oleracea var. alboglabra (cv. “Siji Xianggu jie lan” [“SX”]) seeds was similar with seed coat surface of B.oleraceae var. capitata f. alba cv. "Slava". A scanning electron microscopic study of Chinese broccoli pollen (cv. “SX”) revealed the formation of colpate pollen with ellipsoidal shape with a size of 32.9 ± 0.76 x 17.8 ± 0.42 μm, characterized by foveolate ornamentation with a length-to-diameter ratio – 1.85.The duration of the period from emergence stage to thickening of a stalk and flower-bud formation of cv. “SX” continued for 49-54 days. Сlose correlation was established between the largest diameter of the stem and the length of the leaf petiole (r=0,87, p < 0,001) and between the length of the leaf petiole and the weight of the stem (r=0,77, p < 0,001). As a result of molecular screening of Chinese broccoli using 5 SSR markers (Na10D09, Ol12F02, Ra2E12, BC 7 и BC 65) the greatest polymorphism was in the test with the BC 7 marker - five alleles from 160 to 295 bp in size. In the “SX” variety single flowering (10%) occurred on 59 ... 63 day and mass flowering (75%) – on 65 ... 68 day. The stem part of B. oleracea var. alboglabra is a fairly good source of vitamin C, accumulating as much as 32-46 mg/100 g, and also increased concentration of K, Ca, Mg and Cu. At the end of the season the fruits, together with the phytomass of stems are well-seasoned for 3-4 weeks forming viable seeds with germination above 85% corresponding to the Russian state standard (GOST 32592-2013) for white cabbage seeds.